Aggregate Implications of Barriers to Female Entrepreneurship - Gaurav Chiplunkar; Pinelopi Koujianou Goldberg (Institute of Labor Economics (IZA), 2024)
We develop a framework for quantifying barriers to labor force participation (LFP) and entrepreneurship faced by women in India. We find substantial barriers to LFP, and higher costs of expanding businesses through the hiring of workers for women entrepreneurs. However, there is one area in which female entrepreneurs have an advantage: the hiring of female workers. We show that this is not driven by the sectoral composition of female employment. Consistent with this pattern, policies promoting female entrepreneurship can significantly increase female LFP even without explicitly targeting female LFP. Counterfactual simulations indicate that removing all excess barriers faced by women entrepreneurs would substantially increase the fraction of female-owned firms, female LFP, earnings, and generate substantial gains for the economy. These gains are due to higher LFP, higher real wages and profits, and reallocation: low productivity male-owned firms previously sheltered from female competition are replaced by higher productivity female-owned firms previously excluded from the economy.
Keywords: J16; J70; O17; O40; 330; female entrepreneurship; gender discrimination; misallocation; economic development